Phenanthroline‐Fused Pyrazinacenes: One‐Pot Synthesis, Tautomerization and a RuII(2, 2′‐bpy)2 Derivative. Issue 22 (29th May 2018) - Švec, Pavel; Webre, Whitney A.; Richards, Gary J.; Labuta, Jan; Wakayama, Yutaka; Miklík, David; Karr, Paul A.; Mori, Toshiyuki; Ariga, Katsuhiko; D'Souza, Francis; Hill, Jonathan P.
Abstract : We report the one‐pot synthesis of a phenanthroline‐fused pyrazinacene derivative (6, 13‐dihydrodipyrido[3, 2‐a:2′, 3′‐ c ]‐5, 6, 7, 8, 11, 12, 13, 14‐octaazapentacene‐9, 10‐dicarbonitrile) and its behaviour under alkylating conditions used to improve solubility. Tautomerization of the starting pyrazinacene due to the presence of a reduced pyrazine ring contained within an octaazatetracene chromophore led to mixtures of isomers, and factors affecting the relative yields of these isomers were considered. Isomer population can be described by a two‐step reaction model where initial N‐alkylation affects the reactivity of the remaining nitrogen atoms available for subsequent alkylation. A discrete soluble non‐isomerizable phenanthroline‐fused pyrazinacene was also prepared and the activity of its Ru(bpy)2 complex as a photosensitizer for dye‐sensitized solar cell application was investigated. The compounds reported illustrate the unusual reactivity of reduced pyrazinacenes and also their potential as photosensitizers. Abstract : Unsymmetrically substituted dihydrooctaazapentacenes were prepared in one pot and their tautomeric processes investigated by N ‐ alkylative fixing. A Ru II (2, 2′‐bpy)2 derivative of a related phenanthroline‐fused pyrazinacene was found to be active for photosensitization in dye‐sensitized solar cells.